Nucleation density and pore size tunable growth of ZnO nanowalls by a facile solution approach: growth mechanism and NO2 gas sensing properties. Issue 6 (20th January 2020) - Li, Chun; Yu, Lingmin; Fan, Xinhui; Yin, Mingli; Nan, Ning; Cui, Le; Ma, Shuai; Li, Yuan; Zhang, Bo
Abstract : Nanowalls are novel nanostructures whose 3D porous network morphology holds great potential for applications as gas sensors. Abstract : Nanowalls are novel nanostructures whose 3D porous network morphology holds great potential for applications as gas sensors. The realization of such a nanowall-based gas sensor depends directly on the comprehensive understanding of the growth mechanism of the nanowalls. We induced nucleation density and pore size evolution by increasing the dipping and growth times. The investigation indicates that the 3D porous ZnO nanowalls consist of a seed layer of ZnO nanoparticles and a growth layer of the vertically grown ZnO nanosheets. The seed layer nucleation density dominance is driven by the dipping time. The pore size and the height of the as-grown ZnO nanowalls are determined by varying the growth time. Possible growth mechanisms governing the physical characteristics of the synthesized ZnO nanostructures in the solution process are proposed and discussed. The gas sensor that was fabricated from the ZnO nanowall structure exhibited strong dependence on the microstructure, which was mainly determined by the preparation conditions.